2008
DOI: 10.1002/jbm.a.32129
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical processes of nucleation and growth of calcium phosphate on titanium supported by real‐time quartz crystal microbalance measurements and X‐ray photoelectron spectroscopy analysis

Abstract: Real-time, in situ electrochemical quartz crystal microbalance (EQCM) measurements are conducted to better understand the electrocrystallization of calcium phosphates (CaP) on CP-Ti. X-ray photoelectron spectroscopy is used to identify the exact phase deposited, so that reliable estimation of the electrochemical processes involved is made. Analysis of the integrated intensity of the oxygen shake-up peaks, in combination with the determination of Ca/P and O/Ca atomic ratios, enables to determine unambiguously t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 38 publications
3
58
0
Order By: Relevance
“…Afterwards, it became progressive and accompanied by a three-dimensional growth [400]. Data are available that ECD of CDHA occurs via intermediate formation of an OCP precursor phase [401]. Presumably, this might be a reason, why the electrodeposited CDHA coatings were found to consist of two distinct layers [402].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Afterwards, it became progressive and accompanied by a three-dimensional growth [400]. Data are available that ECD of CDHA occurs via intermediate formation of an OCP precursor phase [401]. Presumably, this might be a reason, why the electrodeposited CDHA coatings were found to consist of two distinct layers [402].…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Eliaz et al [183,184,185] reported several findings that may support the presence of a precursor phase (most likely OCP, although ACP was not excluded) in the process of electrocrystallization of HAp. Real-time, in situ electrochemical quartz crystal microbalance (EQCM) measurements revealed two phenomena during the early 11 min of deposition: (1) incubation time required for the local pH to increase; and (2) formation of a precursor phase with lower mass density and higher charge density.…”
Section: Transient Precursor Phasesmentioning
confidence: 99%
“…Eliaz et al [6][7][8][9][10][11][12][13] have reviewed the advantages of electrodeposition of HAp and studied different aspects of electrocrystallization of HAp on commercially pure Ti (CP-Ti) and Ti-6Al-4V, including the effects of bath pH and operating conditions, nucleation and growth, structure, chemistry and surface morphology, corrosion behaviour and in vivo performance. In one of these studies [7], the need for improving the adhesion of the coating to the substrate, on one hand, and accelerating the bone growth during the first few days post-operation, on the other hand, was noted.…”
Section: Introductionmentioning
confidence: 99%